Grain-boundary character distribution and correlations with electrical and optoelectronic properties of CuInSe2 thin films. (1st October 2016) - Abou-Ras, Daniel; Schäfer, Norbert; Rissom, Thorsten; Kelly, Madeleine N.; Haarstrich, Jakob; Ronning, Carsten; Rohrer, Gregory S.; Rollett, Anthony D.
Abstract: Thin-film solar cells based on polycrystalline Cu(In, Ga)Se2 absorbers exhibit record conversion efficiencies of up to 22.6%. There is still a lack of a quantitative connection between the grain-boundary character distribution (GBCD) and the corresponding electrical and optoelectronic properties. The present work uses microstructural data from a CuInSe2 thin film acquired by electron backscatter diffraction (EBSD) to evaluate the GBCD. The most prominent features of the GBCD of CuInSe2 are Σ3 twin boundaries and the Σ9 and Σ27a symmetric tilt grain boundaries. Moreover, combining EBSD with electron-beam-induced current and cathodoluminescence (measurements on the same identical area) on a CuInSe2 /Mo/glass stack provide the means to relate the grain-boundary character with the corresponding electrical and optoelectronic signals across the grain boundary. In part, determining this relationship is accomplished by means of correlation analysis using measurement data from more than 100 grain boundaries. However, the crystallographic, electrical and optoelectronic data showed no strong correlations, which is attributed to atomic reconstruction found in atomic planes adjacent to planar defects in polycrystalline CuInSe2 thin films and corresponding reductions of excess charge densities at these defects. Graphical abstract: